Estudio de factibilidad para la creación de una empresa especializada en la venta de productos y servicios para la atención de las mascotas con formato de autoservicio en la ciudad de Armenia. (2011)
This is a project specializing in the care with products and services for pets. The project is designed to meet the demands of the owners of pets belonging to levels 3, 4, 5 and 6, where is provided with a comprehensive service, with the characteristic that is the same consumer who take purchasing decisions when you are in a store divided by categories and specialized, such as a self service. Main objective is to determine whether the project is viable to start its activities in the city of Armenia, through specific goals such as the study of market, technical, administrative, legal, environmental and financial. They are used as basic principles of the Administration, those who describes Henry Fayol. The type of research is descriptive using the deductive method. The Constitution of the company is governed under Colombian law. The main conclusion reached with this project is that the realization of this is feasible and viable for any investor, demonstrating that its profitability is above the one offered in the market.